Case Report: The Experience of Managing a Moderate ARDS Caused by SARS-CoV-2 Omicron BA.2 Variant in Chongqing, China: Can We Do Better? - Peng, Junnan; Li, Qiaoli; Dong, Jing; Yuan, Guodan; Wang, Daoxin (Frontiers in Medicine, 2022)
Background The severe coronavirus disease 2019 (COVID-19) pandemic is still raging worldwide, and the Omicron BA.2 variant has become the new circulating epidemic strain. However, our understanding of the Omicron BA.2 variant is still scarce. This report aims to present a case of a moderate acute respiratory distress syndrome (ARDS) caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) Omicron BA.2 variant and to discuss some management strategies that may benefit this type of case. Case Presentation A 78-year-old man, who had four negative nucleic acid tests and a fifth positive, was admitted to our hospital. This patient was generally good upon admission and tested negative for anti-SARS-CoV-2 antibodies even after receiving two doses of the COVID-19 vaccine. On the 7th day of hospitalization, he developed a moderate ARDS. Improved inflammatory index and decreased oxygen index were primarily found in this patient, and a series of treatments, including anti-inflammation and oxygen therapies, were used. Then this patient’s condition improved soon and reached two negative results of nucleic acid tests on the 18th day of hospitalization. Conclusion At-home COVID-19 rapid antigen test could be complementary to existing detection methods, and the third booster dose of COVID-19 vaccine may be advocated in the face of the omicron BA.2 variant. Anti-inflammatory and oxygen therapies are still essential treatments for ARDS patients infected with SARS-CoV-2 Omicron BA.2 variant.